Pairing Fiction and Nonfiction Texts to Promote Literacy and Language Development of Adolescent English Learners. Issue 6 (2nd November 2019) - Ward, Natalia; Schell, Robin Foster; Brown, Clara Lee; Thomason, Betty
Abstract: Based on the relevant research that highlights the impact of pairing fiction and nonfiction texts around a specific theme or a topic for enhanced motivation and reading comprehension for English learners (ELs), this article describes ways to combine texts of various genres to promote ELs' language and literacy development. A middle school example of a lesson on chocolate exemplifies how pairing a number of fiction and nonfiction texts supports differentiation and multiple opportunities for writing.